Design, synthesis and structure–activity relationship studies of novel and diverse cyclooxygenase-2 inhibitors as anti-inflammatory drugs. (December 2014) - Hayashi, Shigeo; Ueno, Naomi; Murase, Akio; Takada, Junji
Abstract Because of the pivotal role of cyclooxygenase (COX) in the inflammatory processes, non-steroidal anti-inflammatory drugs (NSAIDs) that suppress COX activities have been used clinically for the treatment of inflammatory diseases/syndromes; however, traditional NSAIDs exhibit serious side-effects such as gastrointestinal damage and hyper sensitivity owing to their COX-1 inhibition. Also, COX-2 inhibition-derived suppressive or preventive effects against initiation/proliferation/invasion/motility/recurrence/metastasis of various cancers/tumours such as colon, gastric, skin, lung, liver, pancreas, breast, prostate, cervical and ovarian cancers are significant. In this study, design, synthesis and structure–activity relationship (SAR) of various novel {2-[(2-, 3- and/or 4-substituted)-benzoyl, (bicyclic heterocycloalkanophenyl)carbonyl or cycloalkanecarbonyl]-(5- or 6-substituted)-1H-indol-3-yl}acetic acid analogues were investigated to seek and identify various chemotypes of potent and selective COX-2 inhibitors for the treatment of inflammatory diseases, resulting in the discovery of orally potent agents in the peripheral-inflammation model rats. The SARs and physicochemical properties for the analogues are described as significant findings. For graphical abstract: see Supplementary Material. (www.informahealthcare.com/enz)